And After Many Days - Ile, Jowhor (Nigeria, 2016)
And After Many Days is a novel of childhood, of the delicate, complex balance of power and love between siblings; the unique ecosystem of a family. It is also a potrait of a society, as the old world gives way to a new status quo...
Keywords: Cultural Heritage; Family Life; Fiction